2014
DOI: 10.4034/pboci.2014.144.03
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Association between Dental Caries, Obesity and Sensory Characteristics in Students Living in Southern Brazil

Abstract: Objective: To investigate possible associations between dental caries, obesity, sweet taste preference and sensitivity to bitter taste in children and adolescents. Material and Methods: This is a cross-sectional study with a sample of 462 schoolchildren aged 6-15 years enrolled in public schools of Pato Branco, PR. Their oral conditions were examined by adopting the criteria of the World Health Organization. Nutritional status was assessed using anthropometric criteria, adopting the reference standards of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 21 publications
0
14
1
Order By: Relevance
“…Although the vast majority of adolescents with high BMI in this study have presented caries experience (83.3%), there was no statistically significant association between these variables, unlike other Brazilian study that showed lower DMFT index in a obese children and adolescent group [34]. Another study that examined the relationship between BMI and dental caries also found no association between these variables [29], although its sample included both genders and different age group (10-12 years).…”
Section: Discussioncontrasting
confidence: 44%
“…Although the vast majority of adolescents with high BMI in this study have presented caries experience (83.3%), there was no statistically significant association between these variables, unlike other Brazilian study that showed lower DMFT index in a obese children and adolescent group [34]. Another study that examined the relationship between BMI and dental caries also found no association between these variables [29], although its sample included both genders and different age group (10-12 years).…”
Section: Discussioncontrasting
confidence: 44%
“…Tw e n t y -t h r e e s t u d i e s t e s t e d t h e association bet ween overweight and dental caries. 12,36,29,30,32,34,35,37,39,43,44,47,48,52,53,[55][56][57][58][59][60][61]66 Of these, 21 found no association between the two variables investigated in children/adolescents. 12,36,29,30,32,34,37,39,[43][44][45]48,[51][52][53][56][57][58][59][60]66 Three studies concluded that overweight children/ adolescents were less likely to exhibit dental caries than their normal weight peers.…”
Section: Results Of Individual Studies Overweight Vs Dental Cariesmentioning
confidence: 95%
“…12,36,29,30,32,34,35,37,39,43,44,47,48,52,53,[55][56][57][58][59][60][61]66 Of these, 21 found no association between the two variables investigated in children/adolescents. 12,36,29,30,32,34,37,39,[43][44][45]48,[51][52][53][56][57][58][59][60]66 Three studies concluded that overweight children/ adolescents were less likely to exhibit dental caries than their normal weight peers. 47,55,61 Obesity vs. dental caries Twenty-three studies tested the association between obesity and dental caries.…”
Section: Results Of Individual Studies Overweight Vs Dental Cariesmentioning
confidence: 95%
See 2 more Smart Citations